Perception-action coupling in infants with down syndrome: Effects of experience and practice - Polastri, Paula F. [UNESP]; Barela, José A. [UNESP] (My University, 2005)
This study examined the effects of experience and practice on the coupling between visual information and trunk sway in infants with Down syndrome (DS). Five experienced and five novice sitters were exposed to a moving room, which was oscillated at 0.2 and 0.5 Hz. Infants remained in a sitting position and data were collected on the first, fourth, and seventh days. On the first day, experienced sitters were more influenced by room oscillation than were novices. On the following days, however, the influence of room oscillation decreased for experienced but increased for novice sitters. These results suggest that the relationship between sensory information and motor action in infants with DS can be changed with experience and practice.
Keywords: body movement; coordination; Down syndrome; experience; exposure; human; infant; information processing; mathematical analysis; motor activity; motor development; motor performance; oscillation; perception; sensory analysis; sitting; visual information